Multi-site churches : guidance for the movement's next generation - McConnell, Scott (Nashville, Tenn. : B & H Publishing Group, 2009)
Based on research of forty congregations that have grown by opening one or more additional worship locations, Multi-Site Churches provides the next generation of believers interested in this same type of growth with practical insights about how and when to proceed. Common practices and mistakes to avoid are explained, and first-person advice and anecdotes from leading multi-site church pastors offer an advantage for when a church considers whether or not to follow this path of ministry. --From publisher's description.
Why multi-site? -- The pieces that need to come together -- Knowing who you are and what matters -- Decisions that define your multi-site church -- Priority one : finding the leader -- Developing a team of leaders -- Where do you launch? -- How do you communicate multi-site effectively? -- What has to change within your staff? -- Leadership development -- Keeping the sites connected -- Specific types of new sites.
Includes bibliographical references.
Keywords: Multi-site churches